PENGARUH JENIS TANAH DAN DOSIS PUPUK UREA TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea canephora Pierre) - Boidi Irianto Juandri Manik; Muhammad Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this study is to observe the interaction between the types of soil and the fertilizer dose of Urea which is for the growth of the seedlings of Robusta coffee (Coffea canephora Pierre). This research has been condected experimentaly of Agriculture Universitas Riau for 4 months since November to March 2017. The research was arrange in a Completely Randomise Design (CRD) with 2 factors. From both factors, it was obtained 9 combination treatments which were repeatedly 3 times. There were 27 treatments in the experiment. Each experiment consisted of 3 seedlings, So it were 81 seedlings and all seedlings were observed. The treatment in this research was the types of soil (Inceptisol, PMK  and Peat) and the fertiliizer dose of Urea (0 g, 5 g and            10 g). The observed parameter was the height of the seedlings, the number of leaves, stem diameter, the area of widest leaf, the root volume, ratio of the root canopy and the dry weight of seedlings. The data was analyzed with Anova and Duncan’s at level 5%. The result showed that there was no interaction effect between the types of soil and the fertilizer dose of Urea on the seedlings of Robusta coffee except for the stem diameter and the root volume. The combination of PMK soil with Urea dose 5 g gave much better growth to seedlings. Types of soil produced the same growth to the 7 month old of Robusta coffee seedlings but it is better on the peat soils.Urea at dose 5 g/seedling gave the best growth for seedlings. Keyword: Types of Soil, Urea, Seedlings of Robusta coffee